Implementasi Model Pembelajaran Think-Pair-Share Berbasis RME dalam Upaya Meningkatkan Prestasi Kelas VII D SMPN 2 Kumai - Nur Hayati (Anterior Jurnal, 2022)
The learning model that has been applied so far is the conventional learning model, in which the teacher dominates the learning activities, and the activeness of the students is lacking. The problem in this study is whether the Think-Pair-Share learning model based on RME on the subject of Square and Rectangles can improve achievement, motivation, and math activities in learning mathematics for grade VII students of SMP Negeri 2 Kumai in the 2019/2020 school year. Learning is carried out in 2 cycles. Cycle I on square material, cycle II on rectangular material. The data obtained were analyzed descriptively and t-test. Based on the results of the study, there was an increase in achievement, activity, and learning motivation of class VII students of SMP Negeri 2 Kumai for the 2019/2020 school year. With suggestions, the teacher should choose the RME-based TPS cooperative learning model in the mathematics learning process, especially TPS on square and rectangular material to improve student achievement.